Stand up : caracterização de um gênero oral sob a perspectiva da análise de discurso crítica (ADC) - Andrade, Valdete Aparecida Borges (2017)
Facing the scarcity of research that focuses on oral genres, I felt instigated to characterize a new and emerging genre in Brazil, the stand up. I believe that this research is necessary and relevant because it can reveal important aspects of the functioning of this genre, of the social practices of which it is a part of it, and of others linked to it, while at the same time promote further discussions about the genres. The general objective of this research is to characterize the stand up by analyzing its textual-discursive aspects and the social practices of which it is part of it. The specific objectives are: a) to identify if there is a predominant pre-genre in the stand up; b) to examine from which genre chain the stand up is part of it; c) to investigate if there is a mixture of genres in the stand up; d) to find out from which communicative technologies this genre depends on; e) to observe the elements that compose the genre stand up and its effects in the construction of humor; f) to search what stereotypes come into their constitution and how they are represented by the comedians; g) to identify, by applying a questionnaire, how the comedians define and characterize the stand up genre; h) to investigate what causes the laughter in the stand up. To achieve these goals, I refer to the proposal of Fairclough (2003), in the area of Critical Discourse Analysis (CDA), to the contributions of Raskin (1979, 1985), Attardo and Raskin (1991), Travaglia (1989a, 1989b, 1990, 1991, 2007, 2015), Propp (1992), Bergson (2001) and Freud (1905), for humor studies, Travaglia et al (2013) and Dolz and Schneuwly (2004) to deal with oral genres, and to the assumptions of the qualitative methodology, based on Bauer, Gaskell and Allum (2002), Flick (2009a, 2009b), Silverman (2009) and Johnson (2010). In order to broaden perspectives to look at my research object, I turn to the triangulation of theory and data collected and generated. In this research, I adopt Fairclough's (2003) proposal to analyze the ways in which discourse appears in social practices - modes of acting, representing and being - articulated to the three meanings - actional, representational and identificational. Concurrent with the analyzed meanings, I identify how humor is built in the stand up based on the six humor categories proposed by Travaglia (1989a) and in the creativity subcategory elaborated by Sousa (2012). As a result, I identified the following characteristics that stand out most in stand up: the use of irony, exaggeration, complicity mechanisms, use of stereotypes, creativity and absurd and cleverness scripts; informal language with excessive use of profanity; association of verbal and nonverbal language; unpublished and original text; diversity of themes; use of the pre-gender essay (commentary) merged with the humorous, together with the description and the narration. This study evidences CDA's potential for genre analysis and constitutes an important contribution to this theoretical field and especially to the characterization of other oral genres. With this research, I believe I have achieved a significant characterization of the stand up.